Ocorrência de mosca-branca em Annona squamosa no estado de São Paulo - Garcia, Maria José De Marchi (2013)
In Brazil the knowledge about the geographical distribution and host plants of whiteflies (Hemiptera: Aleyrodidae) is limited, mainly on crops. In this communication, the occurrence of Aleurodicus mirabilis (Cockerell, 1898) in high infestations in custard apple (Annona squamosa Linnaeus, 1753) is recorded in the state of São Paulo, Brazil.